Oesophageal Lichen Planus: Case Series and Review of the Literature - Nerea Manzanares; Andrea Molina-Alvarez; Mar Iglesias; Juan Enrique Naves; Ramon M. Pujol; Sonia Segura (Acta Dermato-Venereologica)
Lichen planus affects 0.5% to 2% of the population. The involvement of the oesophagus is a rare manifestation with high morbidity and risk of malignancy. Clinical characteristics and diagnostic-therapeutic strategies were reviewed. A retrospective study of clinical-pathological characteristics, endoscopic findings, and follow-up of patients with oesophageal lichen planus treated at a tertiary hospital during 2006–2023 was conducted. Nine patients (1 man, 8 women) with a median age of 76 years were included. All patients had oral lichen planus. Dysphagia was the initial symptom, being the first manifestation of the disease in 2 cases. All presented lesions in the oral oesophagus with fibrous rings, stenosis, and mucosal denudation. Histological changes of the lichenoid type were observed in 8/9. After a median follow-up of 2 years, no progression to oesophageal squamous cell carcinoma was observed. Swallowed glucocorticoid therapy, proton pump inhibitors, prokinetics, and oesophageal dilatations were prescribed. Eight out of 9 patients showed partial improvement with clinical stabilization. Oesophageal lichen planus is an infrequent and underdiagnosed disease. Its diagnosis may be based on endoscopic features, histopathology, and direct immunofluorescence. The correct management is often challenging, but necessary because this entity has been associated with oesophageal squamous cell carcinoma